Hypercholesterolemia and Alzheimer's disease [Hiperkolesterolemi ve Alzheimer hastalıǧı] - (:unkn) unknown (Turkiye Klinikleri, 2008)
Alzheimer's disease is characterized by the accumulation of amyloid-β peptides in senile plaques and protein aggregates with regional accumulation of hyperphosphorylated tau in neurofibrillary tangles and a dysfunction of the ubiquitin-proteasome system which degrades oxidatively damaged proteins. There is considerable evidence consistent with the importance of oxidative stress in the pathology of Alzheimer's disease and the accumulation of free radicals, leading to excessive lipid peroxidation, oxidative modification of proteins in the brain. Current experimental evidence suggests that an initial source of oxidative stress, such as high cholesterol, may initiate amyloid-β formation; which by itself is another potent source of oxidative stress in Alzheimer's disease. © 2008 by Türkiye Klinikleri.
Keywords: Alzheimer disease; Hypercholesterolemia; Oxidative stress